(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda is the sea of knowledge and to get a pearl out of it one should make a good effort to ensure the curiosity in Human Anatomy specially regarding “Gudavalitrye”. To elaborate the description of “Guda‟ and to certitude “Gudavalitrye” descriptions are illustrated in Modern and Ayurvedic texts. I have tried to correlate the layers of Guda as described in Ayurvedic text in scattered form with modern text to certitude Sushrutokta- “Gudavalitrye’’. In ancient eras Acharyas used to do Sambhasa Parishad before drawing any conclusion. “Tadvida Sambhasa” is said to be the best method of enhancing knowledge according to Charkacharya, which indicate the importance of the discussion in the research work. After thorough discussion of all the observations found throughout the research work, one can draw a definite conclusion. Acharya Charaka described that “A hypothesis can only call principle when it is gone through inquisition and got approved by many experts to give a right judgement.”